Penerapan Metode Al-Miftah dalam Meningkatkan Kemampuan Membaca Kitab Fatkhul Qorib Santri Putra Kelas Takhosus Dipondok Pesantren Hidayatul Mubtadiin Jati Agung Kabupaten Lampung Selatan Tahun Pelajaran 2024/2025: Penelitian - Wahidatussa’diyah, Binti; Feri Fernadi, Muhammad; Sa’diyah, Halimatus (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The Al-Miftah method is a learning strategy designed to facilitate students (santri) in understanding Arabic grammar rules and enhancing their skills in reading unvowelized classical Islamic texts (kitab kuning). Pondok Pesantren Hidayatul Mubtadiin is one of the Islamic educational institutions that has implemented this approach. The objectives of this study are: 1) To identify the implementation of the Al-Miftah method in improving the ability to read the Fathul Qarib book among Takhassus class students at Pondok Pesantren Hidayatul Mubtadiin, Jati Agung, South Lampung, in the 2024/2025 academic year. 2) To examine the process of using the Al-Miftah method in the learning of Fathul Qarib reading in the same class.This research employs a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. Data analysis is carried out in three stages: data reduction, data presentation, and drawing conclusions. To ensure data validity, four techniques are used: credibility, transferability, dependability, and confirmability.The findings of the study reveal two main points. First, the application of the Al-Miftah method has proven effective in enhancing students’ ability to read the Fathul Qarib book at Pondok Pesantren Hidayatul Mubtadiin. This is evidenced by the improved ability of students to comprehend the content, analyze sentence structure, and accurately translate the text. Second, the teaching process using the Al-Miftah method is carried out gradually and systematically, starting from the introduction of nahwu and sharaf rules, the use of symbols or syakal (diacritical marks), practical reading exercises, and reinforcement through contextual learning.